Sosialisasi Terkait Pentingnya Ergonomi pada Ruang Unit Kerja Rekam Medis di Puskesmas Baktiya Barat, Kecamatan Baktiya Barat, Kabupaten Aceh Utara - Mansura Feby Amanda; Tina Aharani (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Community health services are the most important part of supporting community health. Puskesmas is a health institution that is very close to the community. Therefore, it is important to pay attention to supporting facilities and infrastructure in the medical records work unit such as work equipment, work procedures, work processes or systems, work environment, employee physiology and psychology so that medical records officers more productive at work. Based on observations made at the West Baktiya Community Health Center, it was found that the area of the medical records unit was 5 x 5 m2 with a ceiling height of 3 m, using a white ceramic floor, there were 6 windows, 1 door, 2 staff work desks and 3 cupboards for Save correspondence and other important documents. Lighting in the medical records unit room is 259 lux, noise is 53.3-62.0 dB, temperature in the medical records unit room is 33.1oC and humidity is 70%. In the medical records unit room there are no chemical substances in solid, liquid or gas form, and there are also no vectors or disease-carrying animals such as flies, mosquitoes, cockroaches and rats. The aim of this activity is to provide outreach regarding ergonomics in the medical records work unit at the West Baktiya Community Health Center. The implementation method consists of planning, implementation actions, evaluation and activity report preparation stages. The result of this service is that it can increase the knowledge of medical records officers and other healt